Plan de exportación para papilla de quinua orgánica en presentación “ready to eat” a Paises Bajos - Toscano Tello, Juan Antonio (2019)
Currently, a healthy lifestyle trend is being lived not only in Peru but throughout the world. This new concept is related to a balanced diet, exercise and concern for personal care to lead a more pleasant life. The enormous biodiversity that Peru offers in agricultural products, has made Andean grains or also called Super Foods, the most requested and demanded in the international market. Grain quinoa in its different varieties, including red, black, tricolor and white quinoa, are one of the most sought-after Andean grains in the United States and Europe. Faced with this new business opportunity, this project proposes an innovative product with added value, made from organic white quinoa. It is a trilaminated sachet that contains 150gr precooked white quinoa (porridge) ready to eat. To determine the viability of the aforementioned product, the PESTE analysis was carried out and the key characteristics of the destination market were evaluated, which shows the acceptance and demand of the product in the Netherlands, the market chosen for the export plan. An operations plan of the areas involved was made to obtain the finished product, determining objectives, strategies and key goals to generate value in the production chain. On the other hand, the balance of the operational plan for the start-up of the export project was determined, concluding by means of a decision matrix, that a production line must be implemented. Finally, a comprehensive logistics plan for the export of the product is presented, determining the processes and evaluating key operators in this last part of the chain to achieve the four main objectives: cost reduction, time control, capital reduction and service improvement. . Making the right decisions to achieve competitive advantage depends on the relationship between the strategies and objectives and goals set by the company.